RETRACTED ARTICLE: Recombinant human keratinocyte growth factor attenuates apoptosis in elastase induced emphysematous mice lungs. (2nd January 2017) - Kotnala, Sudhir; Baghel, Sumit; Verma, Deepali; Tyagi, Amit; Muyal, Jai Prakash
Abstract : We, the Editor and Publisher of the Inhalation Toxicology, have retracted the following article: Sudhir Kotnala, Sumit Baghel, Deepali Verma, Amit Tyagi & Jai Prakash Muyal. Recombinant human keratinocyte growth factor attenuates apoptosis in elastase induced emphysematous mice lungs (2017). Inhalation Toxicology, 29:1 pages 23–31. DOI: 10.1080/08958378.2016.1272653 After publication of this article, concerns were raised to the Editor and Publisher regarding apparent repeating elements in the comet assays in Figure 3A. Subsequent examination of Figure 3A also raised concerns about a comet assay tail in Figure 3 ES treatment, cell number 5 (bottom row ES label), which appeared to point in an unusual direction compared to the rest of the comet assays in the treatment. Finally in Figure 7, there were concerns that the data in the Western blots do not translate to the relative density plots and there were no apparent loading controls. The authors were contacted and, while they did respond, they were unable to provide the original images for Figure 3. We were also unable to verify the authenticity of the new data for Figure 7 which they provided, which leads us to have concerns about the overall findings of the article. The authors were also unable to provide adequate evidence of formal ethical approval for the animal research carried out. Given the extent of these concerns, this article is being retracted. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The corresponding author listed in this publication has been informed and the authors have agreed to retract the article. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as 'Retracted'.